2022
DOI: 10.3390/dj10060094
|View full text |Cite
|
Sign up to set email alerts
|

Does Low-Taper Root Canal Shaping Decrease the Risk of Root Fracture? A Systematic Review

Abstract: Minimal root-canal preparation has been suggested to reduce the risk of root fracture, but as a result, satisfactory cleaning and shaping do not take place. Large-scale taper instrumentation can contribute to removing infected tissue; however, it may weaken the tooth structure. The aim of this systematic review is to evaluate whether root-canal shaping with low-taper instruments decreases the risk of root fracture, compared to high-conicity shaping. A search was performed on Ovid MEDLINE, PubMed, and the Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The crown-down instrumentation technique is preferred for cleaning and shaping these accessory canals, and care must be taken during instrumentation ( Puleio et al, 2022 ). A careful brushing motion is employed away from the furcation area and toward the mesial side of the root.…”
Section: Resultsmentioning
confidence: 99%
“…The crown-down instrumentation technique is preferred for cleaning and shaping these accessory canals, and care must be taken during instrumentation ( Puleio et al, 2022 ). A careful brushing motion is employed away from the furcation area and toward the mesial side of the root.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that reciprocating motion induces lower tensile and compressive stress in the flexed region of the instrument, thus providing greater fatigue resistance compared with continuous rotative movement [ 28 , 29 ]. High-taper instruments, such as the WaveOne Primary (25/0.08), can contribute to deeper infected-tissue removal, achieving the appropriate irrigant penetration level [ 30 ], and a recent systematic review concluded that it is not clear whether a difference in taper angle can determine differences in root fracture resistance; therefore, it is not possible to provide clinical recommendations regarding the use of endodontic instruments with a high (≥6%) or a low (<6%) taper [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential preparation-related root weakening could be reinforced by adhesive resin-based obturation [17][18][19], but long-term studies have shown signi cantly lower success rates compared to obturation with GP and sealer [20,21]. To reduce the risks of crack formation and root fracture, authors instead recommended MIE shaping with le sizes between #20 to #40 and 0.04 to 0.06 tapers, canal morphology dependent [9,10,22]. On the other hand, insu cient canal debridement could lead to treatment failure, particularly in teeth with infected and necrotic pulp.…”
Section: Introductionmentioning
confidence: 99%